CONTENTION BETWEEN RUSSIA AND USA IN CENTRAL ASIA: REASONS AND AFTERMATHES - Єгорова, А.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The article analyzes the influence of Russia and U.S. on the Central Asian region. Particular attention is paid to the conflict of interest of these two great states. The article considers involvement of foreign entities in the domestic politics of Central Asian states on the example of Kyrgyzstan. The intersection of interests occurred in the implementation of color revolutions, placement of military bases, joining to international organizations, etc.